Energy efficiency developments in the manufacturing industries of Germany and Colombia, 1998-2005 (2009)
This paper describes the energy efficiency development in the German and Colombian industrial sectors between 1998 and 2005. Using data at the two- and three-digit levels for the German and Colombian manufacturing industry, the performance of the industrial sector is analysed in terms of energy intensity, value of production, value added, fuel sources and energy costs. It was found that energy consumption in the industrial sector has increased by 2.3% in Germany and 5.5% in Colombia, whereas energy intensity decreased by 12% and 6% respectively during the sample period. A decomposition analysis was performed in order to separate structural, production and intensity effects. It was found that in both countries, the aggregate energy intensity in the industrial sector was highly dependent on the changes in the energy intensive sectors (EISs). The trend is to produce more while consuming less energy. In Germany, structural and intensity effects contributed to energy efficiency improvement, whereas in Colombia, intensity effects dominated over structural effects. Moreover, in both countries the capital intensity and energy prices influenced the changes in the aggregate energy intensity, whereas the changes in labour intensity did not show a clear relationship with the energy intensity results. These results showed the importance of the formulation and adoption of energy policies in the industrial sector, taking into account that several differences in energy efficiency performance exist at the different levels of aggregation and that energy policy instruments ought to encourage cost-effective energy efficiency.